2011
DOI: 10.1093/infdis/jir145
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Variations in CCL3L1 and CCR5 on Tuberculosis in a Northwestern Colombian Population

Abstract: We investigated the association of polymorphisms in CCR5, the major human immunodeficiency virus (HIV)-1 coreceptor, and copy number of its potent ligand CCL3L1 with tuberculosis in 298 individuals from Colombia. The CCR5-HHD haplotype, a known genetic determinant of increased susceptibility to HIV-AIDS, and a high copy number of CCL3L1, a known genetic determinant of enhanced CCL3/CCL3L1 chemokine expression, each associated with presence of tuberculosis. Furthermore, CCR5-HHD was associated with higher CCR5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 16 publications
0
27
1
Order By: Relevance
“…However, surprisingly the association studies of CCL3L1 / CCL4L1 copy number provide no evidence for an association of copy number with clinically active TB in all three populations. A previous study (n = 298) found evidence individuals with CCL3L1 copy numbers greater than the average (CN = 2) were associated with increased susceptibility to active TB in a Colombian population [24]. However our study could not replicate this observation in Peruvian samples despite the greater sample size.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…However, surprisingly the association studies of CCL3L1 / CCL4L1 copy number provide no evidence for an association of copy number with clinically active TB in all three populations. A previous study (n = 298) found evidence individuals with CCL3L1 copy numbers greater than the average (CN = 2) were associated with increased susceptibility to active TB in a Colombian population [24]. However our study could not replicate this observation in Peruvian samples despite the greater sample size.…”
Section: Discussioncontrasting
confidence: 75%
“…The correlation of variants in the chemokine-chemokine receptor pair with TB susceptibility may have been anticipated from functional analyses, but our data does not support this. A recent observation identified that haplotypes in CCR5 associated with increased expression of CCR5 are associated with TB susceptibility in individuals with 2 copies or more of CCL3L1 [24]. Our understanding of the precise role of cytokines in TB infection remains limited (reviewed in [43]) and there is much compensation and overlap of roles due to the complexity of the system.…”
Section: Discussionmentioning
confidence: 99%
“…Chemokines are a family of small (8)(9)(10) proteins that have the ability to attract and activate leukocytes. The biological activities of chemokines are mediated by interactions with their cell-surface receptors that belong to the structurally related seven-transmembrane domain superfamily of proteins [5].…”
Section: Introductionmentioning
confidence: 99%
“…The expression levels of chemokines and their receptors have been found associated with infectious and autoimmune diseases. In recent years, it has been described genetic polymorphisms that affect the levels of expression, and some of them were associated with susceptibility, progression and severity to certain diseases [6][7][8][9]. Moreover, exist experimental evidence that suggest that chemokine and chemokine receptors may contribute to cardiac tissue damage during Chagas disease [10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Mamtani et al (2011) evaluated the effects of CCR5 haplotypes (including CCR5∆32 and eight other CCR5 variants) on tuberculosis in Colombian individuals (Mamtani et al, 2011; Mummidi et al, 2000). The haplotype CCR5 ‐HHD (in which CCR5∆32 wild‐type allele is present; see Table 1 for complete haplotype description) was associated with increased CCR5 expression and was considered a risk factor for tuberculosis (Mamtani et al, 2011).…”
Section: Ccr5 and Ccr5δ32 In Bacterial Infectionsmentioning
confidence: 99%